Gestión y política industrial en sectores de alta tecnología: el caso de los semiconductores - Carter, Shelby H. (1992)
This case analyzes what elements could entail in the United Stated industrial policy, giving a special emphasis on permanent changing modern high-tech industries environment. At the same time, it is sought to demonstrate that the correct orientation should be aimed to the intensive research and closely related to technological developments. It is argued that change and a flexible response are the necessary ingredients of an industrial policy aimed to meet the requirements of this industry. It specifically focuses on semiconductor companies to illustrate what sector like this could entail for public policy. This sector faces in complex ways a situation of continuous change and interaction through all the stages and processes from products. The behavior of this industry leads to misinterpretations and can lead to apply wrong policies.